ANALISA TENTANG KONSEP FEMINISME DALAM ISLAM - Muhamad Basyrul Muvid (Dirosat : Journal of Islamic Studies, 2022)
This article study seeks to analyze in depth the concept of feminism in Islam. The beginning of their creation is the same as that of men. In Islam, women also have the same rights and duties with courtesy. They have the same obligations of worship, receiving punishment and punishment in addition to compensation and bad actions. There are many other areas of Islamic concepts. However, in sustainable development, feminism causes a release for women's lives. In the end, this contradicts the idea of equal rights and obligations between men and women in Islam. Feminism in Islam is a movement to provide equal opportunities to women in the social, economic, political, educational and cultural fields, while remaining women as creatures who must obey men in the household frame. That is, the feminist movement in Islam does not make women out of their nature, which will cause new problems.